THU0536 Remission and Re-Treatment of Patients with Paget's Disease of Bone Treated with Zolendronic Acid – A Single Center 10 Year Experience. (15th July 2016) - Fernandes, S.; Borges, J.; Silva, C.; Simões, E.; Micaelo, M.; Barcelos, F.; Madeira, H.; Vaz Patto, J.; Cunha Miranda, L.; Sousa, M.; Cortes, S.; Faustino, A.
Abstract : Background: Treatment of Paget's Disease of Bone (PDB) has been revolutionized by the use of zolendronic acid (ZA). Patients usually have a dramatic response to treatment with normalization serum alkaline phosphataise (ALP) levels and a longer period of clinical remission, compared with other class agents. Data from long-term use are scarse. Objectives: Evaluate the effectiveness and safety of ZA in PDB patients, as well as remission, re-treatment rates and side effects in our outpatient population since 2005. Methods: A retrospective study of PDB patients treated with 5 mg ZA intravenous infusion at our day-care center. Follow up time, demographic and clinical characteristics, previous therapeutic agents, rate of response, number and reasons of re-treatment(s) and rates of adverse events were collected. A descriptive statistic analysis was made. Results: 48 patients, 60% female, mean age of 75 years, with a median time since the diagnosis of 12.3 years. The disease was poliostotic in 73% of the patients and pelvis (65%), skull (29%) and spine (27%) were the most common pagetic localizations. Deafness was present in 12.5% and 65% had hip involvement. 44% patients had been treated with another biphosphonate agent previously. Response rates were 97.9% at 1 year, 87.2% after 2 years and 95.1% after 3 years. The mean ALP levels before ZA infusion was 290 UI/L and after 112 UI/L. Sixteen patients needed a re-treatment in the period of follow up, minimum of 1 year after the ZA infusion and maximum of 8 years after. 56.3% due to raised of ALP levels and 43.8% due pain/ hip involvement. Four patients needed a third infusion due to hip involvement, and 2 of them a forth infusion due to the same reason. All of the patients re-treated due to hip involvement had severe hip involvement at time of diagnosis. In our population, 2 patients achieved 10 years remission, 5 patients 9 years remission and 10 patients 8 years remission with a single ZA infusion. Recording adverse effects were: 14.6% Flu like symptoms (7 patients), 2% assintomatic hypocalcemia (1 patient) and no reports of osteonecrosis or fractures. All of these effects were reported after the first ZA infusion. Conclusions: In our population, we find high long-term sustained remission rate. Only sixteen patients needed re-treatment. Patients maintained sustained remission up to 10 years of a single ZA infusion. Incidence of adverse events was similar to the reported in the literature. References: Reid IR, Miller P, Lyles K et al. Comparison of a Single Infusion of Zolendronic Acid with Risendronate for Paget's Disease. N Eng J Med. 2005 Set:353(9):898–908 Reid IR, Brown JP, Levitt N et al. Re-treatment of relapse Paget's disease of bone with zolendronic acid: results from an open-label study. Natur BoneKEy Report 2. 2013 Nov: 442: 1–3 Reid IR, Lyles K, Brown JP et al. A Single Infusion of Zolendronic Acid Produces Sustained Remissions in Paget Disease: Data from 6.5 years, JBMR. 2011 Sep 26 (9):2261–70 Devogelaer JP, Geusen P, Daci E et al. Remission over 3 years in patients with Paget disease of bone treated with a single intravenous infusion of 5 mg zolendronic acid. Calcif Tissue Int. 2014 Mar:94(3):311–8 Disclosure of Interest: None declared